1987
DOI: 10.7164/antibiotics.40.991
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure-activity relationships of a new oral cephalosporin, BMY-28100 and related compounds.

Abstract: The synthesis and structure-activity relationships of 7-[D-a-amino-a-(4-hydroxyphenyl)-acetamido]-3-[(Z)-l-propenyl]-3-cephem-4-carboxylic acid (BMY-28100) and its analogs in the 3-and 7-side chains are described. The 3-(substituted-propenyl) groups were introduced by the Wittig reaction of the 3-phosphoniomethyl cephems which were derived from the 3-chloromethyl derivatives. The reaction gave predominantly the cis isomer regarding the 3-side chain. The cis and trans isomers showed characteristic UV and 1H NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, a 45-fold rate enhancement was observed when lactam 3 was coupled with vinyltributylstannane in the presence of the tri-2furylphosphine catalyst system. 1 In a related study 26 aimed at developing an efficient synthesis of antibiotic BMY-28100, 27 Farina showed that the beneficial effects observed upon substitution of TFP for PPh 3 in the Stille reaction may be of general scope. Treatment of vinyl triflate 9 with a variety of organostannanes at room temperature in NMP using ZnCl 2 and the TFP catalyst system smoothly afforded the desired cross-coupled products 10-12 in moderate to excellent yields 28 (Scheme 3).…”
Section: A Discovery Of Tfp As An Exceptional Ligand For the Stille R...mentioning
confidence: 99%
“…Moreover, a 45-fold rate enhancement was observed when lactam 3 was coupled with vinyltributylstannane in the presence of the tri-2furylphosphine catalyst system. 1 In a related study 26 aimed at developing an efficient synthesis of antibiotic BMY-28100, 27 Farina showed that the beneficial effects observed upon substitution of TFP for PPh 3 in the Stille reaction may be of general scope. Treatment of vinyl triflate 9 with a variety of organostannanes at room temperature in NMP using ZnCl 2 and the TFP catalyst system smoothly afforded the desired cross-coupled products 10-12 in moderate to excellent yields 28 (Scheme 3).…”
Section: A Discovery Of Tfp As An Exceptional Ligand For the Stille R...mentioning
confidence: 99%
“…The cleavage of the acetyl residue can be carried out both enzymatically [241] and chemically [242] under mild conditions. Oxidation of alcohols obtained in this way allows preparation of the corresponding 3-formylcephalosporins, which can suffer further transformations such as the Wittig olefination [243] or Barbier-type allylation [244]. 3-Halomethyl cephalosporins can be synthesized via substitution reactions in 3-acetoxy(hydroxy)methyl cephalosporins [245].…”
Section: Reactions For the Transformation Of Functional Groups In Sidmentioning
confidence: 99%
“…In another pioneering paper S. Boettger described the development of a Zymark Py Technology automated system for process optimisation . After having established the robotics system their first test reaction was a room-temperature reaction which is used in the synthesis of a wide variety of oral cephalosporin antibiotics (Scheme ).
2 Phosphine reaction
…”
Section: Overview Of Automated Chemistry In Organic Process Research ...mentioning
confidence: 99%